2016
DOI: 10.1155/2016/6260792
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Thawed Apheresis Fresh-Frozen Plasma Stored for up to 120 Hours at 1°C to 6°C

Abstract: Regulations concerning the storage of transfusable plasma differ internationally. In Canada, plasma obtained from whole blood donations and frozen within 24 hours of phlebotomy (frozen plasma, FP) may be thawed and transfused within 120 hours of refrigerated storage. However, plasma frozen within 8 hours of phlebotomy following apheresis donation (FFPA) must be transfused within 24 hours of thawing and refrigeration. Our objectives were to measure coagulation factors (F) V, VII, and VIII, fibrinogen activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Most of the declines were minor albeit statistically significant when compared to their respective baselines at the time of thaw. The bulk of the decline occurred within the first 24 h post‐thaw which corresponds to the current shelf life when stored at 1–6°C . Although coagulation factors in FFP and RTFP24 at 96 h post‐thaw were mostly within our laboratory's reference ranges, we observed significantly poorer thrombin generation potential in both FFP and RTFP24 at 96 h post‐thaw compared to their respective baselines.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Most of the declines were minor albeit statistically significant when compared to their respective baselines at the time of thaw. The bulk of the decline occurred within the first 24 h post‐thaw which corresponds to the current shelf life when stored at 1–6°C . Although coagulation factors in FFP and RTFP24 at 96 h post‐thaw were mostly within our laboratory's reference ranges, we observed significantly poorer thrombin generation potential in both FFP and RTFP24 at 96 h post‐thaw compared to their respective baselines.…”
Section: Discussionmentioning
confidence: 56%
“…Extending the shelf life of thawed plasma could facilitate the availability of prethawed plasma for massive transfusion protocol and reduce the wastage of thawed plasma. Evidence from studies involving thawed FFP and FP24 has found that coagulation factors were generally maintained within the reference ranges and met quality standards when stored up to 5 days . Similar data on thawed RTFP24 are limited .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, this pooled patient meta‐analysis also delivered results relevant to countries with short FFP storage durations (e.g. 12 months) such as Australia and Canada . For example, FFP is stored for 12 months with most FFP transfused within the first 3 months of storage in Australia.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7][8] However, studies suggest that factor levels in TP are sufficient for its safe use in the treatment of frequently encountered coagulopathies. 4,7,[9][10][11] Plasma transfusion can be associated with both infectious and non-infectious complications. The overall risk of transfusion-transmitted infections (TTIs) is low, but remain a major concern in transfusion medicine, 12 especially untested emerging pathogens.…”
Section: Introductionmentioning
confidence: 99%